High-Performance Thin Film Composite Nanofiltration (NF) Membrane Constructed on Modified Polyvinylidene Fluoride (PVDF) Substrate - Junliang Dong; Qianzhi Sun; Xiaolin Feng; Ruijun Zhang (Membranes)
The inherent hydrophobic nature of PVDF material renders it challenging to establish a stable aqueous hydration layer, thereby limiting its suitability as a substrate for the preparation of nanofiltration (NF) membranes. In this study, we developed a novel modification approach that effectively enhances the hydrophilicity of PVDF substrates through the incorporation of sulfonic acid-doped polyaniline (SPANI) and hyperbranched polyester (HPE) into the PVDF casting solution, followed by cross-linking with trimesoyl chloride (TMC). The introduction of SPANI and HPE, which contain reactive polar amino and hydroxyl groups, improved the hydrophilicity of the substrate, while the subsequent cross-linking with TMC effectively anchored these components within the substrate through the covalent linking between TMC and the reactive sites. Additionally, the hydrolysis of TMC yielded non-reactive carboxyl groups, which further enhanced the hydrophilicity of the substrate. As a result, the modified PVDF substrate exhibited improved hydrophilicity, facilitating the construction of an intact polyamide layer. In addition, the fabricated TFC NF membrane demonstrated excellent performance in the advanced treatment of tap water, achieving a total dissolved solid removal rate of 57.9% and a total organic carbon removal rate of 85.3%. This work provides a facile and effective route to modify PVDF substrates for NF membrane fabrication.